Vitamin D and Atopic Dermatitis in Childhood - Michelangelo Vestita; Angela Filoni; Maurizio Congedo; Caterina Foti; Domenico Bonamonte (Journal of Immunology Research)
Vitamin D features immunomodulatory effects on both the innate and adaptive immune systems, which may explain the growing evidence connecting vitamin D to allergic diseases. A wealth of studies describing a beneficial effect of vitamin D on atopic dermatitis (AD) prevalence and severity are known. However, observations linking high vitamin D levels to an increased risk of developing AD have also been published, effectively creating a controversy. In this paper, we review the existing literature on the association between AD and vitamin D levels, focusing on childhood. As of today, the role of vitamin D in AD is far from clear; additional studies are particularly needed in order to confirm the promising therapeutic role of vitamin D supplementation in childhood AD.